Трудные судьбы подростков - кто виноват? - Панкратов Владимир Васильевич (Молодежи о праве, 1991)
Экземпляры: КХ (20100909) / Инвентарный номер: 986620 / Цена: / Сис.шифр: 67.51 / Авт.знак: Т 78 / ГРНТИ: 10 / ББК: 67.518.8